2013
DOI: 10.1111/nhs.12049
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of adult ventilator‐dependent patients: A meta‐synthesis review

Abstract: Studies exploring the perceptions of patients whose lives are maintained by mechanical ventilation highlight the stressful nature of this type of experience. The objective of this meta-synthesis study was to describe the nature of the experience of adult ventilator-dependent patients. A systematic literature search of English and Chinese databases was undertaken, covering the period between 1970 and 2012. Qualitative research findings were extracted and pooled using the Joanna Briggs Institute Qualitative Asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
(96 reference statements)
1
19
0
Order By: Relevance
“…Patients' experiences of voicelessness during mechanical ventilation were a central theme (Dithole, Sibanda, Moleki, & Thupayagale‐Tshweneagae, 2016; Karlsen, Ølnes, & Heyn, 2018; Tsay, Mu, Lin, Wang, & Chen, 2013; Yang, 2016). Words used to depict the experiences were dependency, vulnerability, isolation, helplessness, uncertainty, distress, and powerlessness; as well as loss of personality, identity, control, and freedom (Karlsen et al., 2018; Tsay et al., 2013; Yang, 2016). Frustration was the word most used to describe the voicelessness: ‘Being voiceless is perhaps the most frustrating experience of mechanically ventilated patients’ (Yang, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients' experiences of voicelessness during mechanical ventilation were a central theme (Dithole, Sibanda, Moleki, & Thupayagale‐Tshweneagae, 2016; Karlsen, Ølnes, & Heyn, 2018; Tsay, Mu, Lin, Wang, & Chen, 2013; Yang, 2016). Words used to depict the experiences were dependency, vulnerability, isolation, helplessness, uncertainty, distress, and powerlessness; as well as loss of personality, identity, control, and freedom (Karlsen et al., 2018; Tsay et al., 2013; Yang, 2016). Frustration was the word most used to describe the voicelessness: ‘Being voiceless is perhaps the most frustrating experience of mechanically ventilated patients’ (Yang, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…It was even suggested that ‘many patients died without fully expressing their needs and wishes about end‐of‐life care or final message to loved ones’ (Yang, 2016). Another research synthesis pointed out that the voicelessness contributed to disorientation (Tsay et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further finding was the many descriptions of discomforts other than pain, possibly dominating because descriptions of actual pain were rare. The majority of these discomforts have been reported on and presented in reviews of the qualitative literature (Cutler et al., ; Egerod et al., ; Tsay, Mu, Lin, Wang, & Chen, ). We found that well‐known discomforts relating to MV, communication difficulties, comprehension and experiencing delusions were often triggered or aggravated by how the patients fluctuated between states of wakefulness.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have studied factors that have a stressful effect on mechanically ventilated patients [ 15 18 ] and have found that one of the worst remembered and most stressful experiences, aside from thirst and pain, is endotracheal tube discomfort [ 19 ]. There are several tools to assess stressors within ICU, and all of them allow us to assess the degree of stress or nuisance experienced by the patient for each factor.…”
Section: Introductionmentioning
confidence: 99%